The Effect of Project-Based Learning Models Aided by Teaching Materials Through Internet Technology to Improve Analytical and Comprehension Mathematical Concepts Ability - Indah Fitria Rahma; Nurlina Ariani Hrp; Syntya Lestari Sinulingga; Amroh Harahap; Tata Suhita Pramesti (Universitas Mercu Buana Yogyakarta, 2022)
The purpose of the study was to determine the effect of the project-based blended learning model with the help of teaching materials through the use of internet technology on increasing analytical skills and understanding concepts, especially the mathematical field of students during the Covid-19 pandemic at SMP Negeri 1 Kotapinang. The research design used a 2 x 2 factorial design with a quasi-experimental type of research. The research population was students of SMP Negeri 1 Kotapinang with a sample of two classes, namely class VIII-2 and VIII-3 with the number of each class being 30 students. The research instrument uses a test of analytical skills and understanding of mathematical concepts with reference to the combination of each achievement indicator. The results of the analysis found that from 30 students in the experimental class there were 8 students with pretest results in the poor category with a percentage of 27% and 22 students in the very poor category with a percentage of 73%. While the results of the post-test showed that 14 students got a special category with a percentage of 47% and 16 students got a very good category with a percentage of 53%. The results of the analysis of statistical testing using the t test at a significance level of = 0.05 obtained t count of 1.25 with a significance value of 0.000 while t table of 1.12. Because tcount ttable (1.25 1.12) and significance 0.05 (0.000 0.05), then H0 is rejected so that the expectation hypothesis is accepted. Therefore, it was concluded that there was a significant effect of the application of the project-based blended learning model on improving students' analytical skills and understanding of mathematical concepts compared to the application of the ordinary learning model.